Educação Social e trajetórias de vida: os signficados do Projeto Criança e Adolescente Feliz (PCAF) para um grupo de jovens de Corumbá (MS). - Hesley Santana Salustiano (2024)
This research was made possible through the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul – Campus Pantanal. The dissertation addresses and analyzes the perceptions of a group of young students, graduates of the Happy Children and Adolescents Program (PCAF), one of the projects developed by the Salesian Mission in the institution called Cidade Dom Bosco, located in the municipality of Corumbá (MS). Cidade Dom Bosco was founded in April 1961 by Father Ernesto Saksida, and through various social projects, it has been operating for more than 60 years serving children, adolescents and young people in social vulnerability. Aware of the importance of the work carried out by the Salesian Mission in Dom Bosco City, we defined the following questions as the central axes of the research: What are the meanings of social and educational projects for young people in vulnerable situations? And what impact did the Happy Children and Adolescents Program (PCAF) have on the subjectivity of young people from Corumba who attended the city of Dom Bosco? In general terms, the purpose of the research was to understand what the PCAF meant in the life trajectories of young people from Corumba who at some point in their lives were socially vulnerable. To achieve this objective, we established a dialogue with a group of PCAF graduates. These graduates accepted the invitation to narrate memories about experiences lived at PCAF and reported their perceptions about the educational work of the Salesians in Cidade Dom Bosco. The set of narratives was recorded in audio, and was later transcribed and interpreted. In the interpretation, we adopted the conception of education present in the work of Paulo Freire and used theoretical references from Pierre Bourdieu Sociology. In the first chapter of the Dissertation we address the conceptions that society produces about young people. In the second chapter I define the research specialties, presenting general aspects of the city of Corumbá and establishing relationships between the city and the Salesian Mission. In the third chapter we interpret fragments of the reports collected from the young research participants. In the final considerations we highlight relevant aspects of the research. Within this scope, the Dissertation pays special attention to the PCAF and the Salesian educational practices implemented in Cidade Dom Bosco, in the municipality of Corumbá. Based on a Social Education experience led by Salesians and aimed at young people in vulnerable situations, the research demonstrates that social educational projects play a crucial role in social inclusion and reducing inequalities, and, at the same time, influence the construction of youthful subjectivities. Keywords: Social Education; Social Projects; Salesians; Youth.